Open-Loop Precoder Design for Spatial Multiplexing Systems in Transmit Correlated MIMO Channels - Jang, Jungyup; Kim, Dong Ho; LEE, YE HOON; Seo, JongSeo (IEEE transactions on vehicular technology, 2017)
The performance of spatial multiplexing (SM) systems is significantly degraded in transmit correlated multiple-input multiple-output (MIMO) channels. In communication systems that are available for feedback, precoding can enhance performance by exploiting channel state information (CSI) at the transmitter. However, broadcasting systems have no reverse channel nor any CSI. Furthermore, channel mismatches in communication systems severely affect performance. For these systems, open-loop precoders that require no feedback CSI were proposed. However, an analytical precoder design method was not presented in the previous works. In this paper, we present an open-loop precoder design method for SM systems with a maximum-likelihood receiver in transmit correlated MIMO channels. We first describe how to design an open-loop precoder using a rotational matrix over the amplitude of the correlation. Our precoder design method is derived by observing the effect of correlation mismatch between the feedback CSI and the actual channel condition on a minimum Euclidean distance-based precoder. Next, we present a method to design an open-loop precoder that takes into account the impact of the phase of the correlation. For this precoder, a phase rotation matrix is added on the rotational matrix, and optimum parameters are obtained by maximizing the worst-case minimum distance for the phase of the correlation. The simulation results illustrate the validity of proposed open-loop precoder in transmit correlated MIMO channels.